2001
DOI: 10.1023/a:1006485726523
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A sheep was dosed three times per day over six consecutive days with 70 g Narthecium ossifragum, and once on the seventh day with 70 g N. ossifragum. Additionally, it was dosed once on days 1-7 with 20 mg of [20,23,23-2H3]sarsasapogenin. After 7 days, the sheep was killed and GC-MS analysis of the free and conjugated sapogenin content in bile, urine, rumen, duodenum, jejunum, colon and rectum samples collected from the sheep, faecal samples collected on days 4-7, and dosed plant material was performed. The N. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…Because only a single sheep was dosed in the trials reported in this paper, care must be exercised when the results presented in Tables and 2 are interpreted. The results are, however, consistent with levels of free and conjugated sapogenins and episapogenins detected in previous dosing trials ( , ). Prior to the use of the methodology in a field trial, there is a need to validate the methodology in a multiple-sheep trial (e.g., n = 3) in which the deuterated subtrate is dosed over an extended time period.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Because only a single sheep was dosed in the trials reported in this paper, care must be exercised when the results presented in Tables and 2 are interpreted. The results are, however, consistent with levels of free and conjugated sapogenins and episapogenins detected in previous dosing trials ( , ). Prior to the use of the methodology in a field trial, there is a need to validate the methodology in a multiple-sheep trial (e.g., n = 3) in which the deuterated subtrate is dosed over an extended time period.…”
Section: Resultssupporting
confidence: 90%
“…Reduction of 1b using sodium borohydride afforded a 1:4 mixture of [2,2,4,4- 2 H 4 ]sarsasapogenin ( 2b ) and [2,2,4,4- 2 H 4 ]episarsasapogenin ( 3b ). The relative contributions of the deuterated genins 2b and 3b in the synthetic mixture are comparable to those of the natural genins 2a and 3a detected in fecal samples following the dosing, in previous trials, of N. ossifragum plant material ( , ). Complete 1 H and 13 C NMR assignments (see Supporting Information) of 1b , 2b , and 3b were derived from detailed analyses of one- and two-dimensional NMR spectral data, including COSY, TOCSY, ROESY, g-HSQC, and g-HMBC spectra.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Investigations of bacterial fermentation have shown that the intestinal degradation of PPD ginsenosides proceeds stepwise via the cleavage of sugar moieties, mainly liberating the monoglycosylated ginsenoside CK [10,41]. However, these intestinal microfloras are very changeable depending on host conditions (such as diet, health, and even stress) [42,43]. Therefore, it is hypothesized that individual differences in ginseng efficacy may be partially associated with the intestinal microflora of patients.…”
Section: Resultsmentioning
confidence: 99%